Rapid effector function of circulating NC16A-specific T cells in individuals with mucous membrane pemphigoid. - Black, A; Seneviratne, S; Jones, L; King, A; Winsey, S; Arsecularatne, G; Wojnarowska, F; Ogg, G (2004)
BACKGROUND: Mucous membrane pemphigoid (MMP) is a chronic blistering skin disease frequently associated with circulating autoantibodies directed to a number of antigens including the NC16A region of BP180. NC16A domain-specific T cells have been identified in the blood of individuals with bullous pemphigoid (BP), pemphigoid gestationis and linear IgA disease, but there are no data investigating the potential role for such T cells in the pathogenesis of MMP. OBJECTIVES: To test the hypothesis that NC16A-specific T cells exist in the peripheral blood of individuals with MMP. METHODS: We isolated peripheral blood mononuclear cells from 10 patients with MMP, 17 with BP and 10 healthy controls and examined the immunogenicity of overlapping peptides spanning the NC16A domain using interferon (IFN)-gamma enzyme-linked immunospot assay. RESULTS: Significant IFN-gamma production was observed in response to the NC16A peptides in two of the patients with MMP and two of the patients with BP but in none of the normal controls. These data suggest that in a minority of individuals with MMP, NC16A domain-specific T cells circulate at sufficiently high frequency to be detectable directly ex vivo and to show rapid effector function. CONCLUSIONS: Overall, these findings are the first to examine the potential role for antigen-specific autoreactive T cells in the pathogenesis of MMP, and confirm that in some individuals the NC16A domain may be an important target antigen.